Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Our platform offers a seamless experience for finding reliable answers from a network of experienced professionals. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

15 (y - 4 ) - 2 ( 9y - 11 ) = 4 (8z - 13)

Sagot :

Answer to the given equation is 32z + 3y = 14.

  • Step 1: Given data: The given equation is 15 (y - 4) - 2 (9y - 11 ) = 4 (8z - 13)
  • Step 2: Solving the above equation,

15y - 60 - 18y + 22 = 32z - 52

- 3y - 38 = 32z - 52

- 3y + 52 - 38 = 32z

- 3y + 14 = 32z

32z + 3y = 14

Hence, we get 32z + 3y = 14

Learn more about solving linear equations, refer:

https://brainly.com/question/2159099

We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.